2021
DOI: 10.3390/polym13091459
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties, Wettability and Thermal Degradation of HDPE/Birch Fiber Composite

Abstract: Wood–plastic composites have emerged and represent an alternative to conventional composites reinforced with synthetic carbon fiber or glass fiber–polymer. A wide variety of wood fibers are used in WPCs including birch fiber. Birch is a common hardwood tree that grows in cool areas such as the province of Quebec, Canada. The effect of the filler proportion on the mechanical properties, wettability, and thermal degradation of high-density polyethylene/birch fiber composite was studied. High-density polyethylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 48 publications
(66 reference statements)
2
7
0
Order By: Relevance
“…Figure 9 and Figure 10 show the thermograms of both kinds of composite using HDPE and PP as a matrix, respectively. The loss of HDPE and PP mass occurred in a single-stage degradation process that occurred over the temperature range of 400–500 °C [ 30 , 31 ]. Comparing the thermograms of both kinds of composites it can be concluded that the interaction between polyolephynic matrix (HDPE and PP) is higher with CFs reinforcement than GTR.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 9 and Figure 10 show the thermograms of both kinds of composite using HDPE and PP as a matrix, respectively. The loss of HDPE and PP mass occurred in a single-stage degradation process that occurred over the temperature range of 400–500 °C [ 30 , 31 ]. Comparing the thermograms of both kinds of composites it can be concluded that the interaction between polyolephynic matrix (HDPE and PP) is higher with CFs reinforcement than GTR.…”
Section: Resultsmentioning
confidence: 99%
“…The pure HDPE was primarily composed of HDPE, which had relatively high thermal stability. 18 The onset temperature of pure HDPE was observed at 441 C; it represented the point at which the thermal decomposition of HDPE began (Table 3). The end-set temperature was observed at 497 C, meaning most of the HDPE material was decomposed.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…1,2 As a result, natural fibre reinforced polymer composites with fibre particulates as filler have been developed. [3][4][5] Natural fibres are gaining popularity as reinforcing materials not only in thermosetting composites but also in thermoplastic polymer composites. Natural fibres or filler materials derived from renewable sources have the potential to serve as biodegradable and biocompatible reinforcements in the polymer sector and also as an alternative to glass or carbon fibre.…”
Section: Introductionmentioning
confidence: 99%